Limited Sufficiency of Antigen Presentation by Dendritic Cells in Models of Central Nervous System Autoimmunity - Wu, Gregory F. (2010)
Experimental autoimmune encephalomyelitis (EAE), a model for the human disease multiple sclerosis (MS), is dependent upon the activation and effector functions of autoreactive CD4 T cells. Multiple interactions between CD4 T cells and major histocompatibility class II (MHCII)+ antigen presenting cells (APCs) must occur in both the periphery and central nervous system (CNS) to elicit autoimmunity. The identity of the MHCII+ APCs involved throughout this process remains in question. We investigated which APC in the periphery and CNS mediates disease using transgenic mice with MHCII expression restricted to dendritic cells (DCs). MHCII expression restricted to DCs results in normal susceptibility to peptide-mediated EAE. Indeed, radiation-sensitive bone marrow-derived DCs were sufficient for all APC functions during peptide-induced disease. However, DCs alone were inefficient at promoting disease after immunization with the myelin protein myelin oligodendrocyte glycoprotein (MOG), even in the presence of MHCII-deficient B cells. Consistent with a defect in disease induction following protein immunization, antigen presentation by DCs alone was incapable of mediating spontaneous optic neuritis. These results indicate that DCs are capable of perpetuating CNS-targeted autoimmunity when antigens are readily available, but other APCs are required to efficiently initiate pathogenic cognate CD4 T cell responses.